The Public Repercussions of Mandatory Audit Rotation and an Empirical Research in the UK Market - Sun, Ding (2006)
The paper focuses on the attitudes of public companies to the mandatory auditor rotation, especially mandatory audit firm rotation. The existing literatures, and empirical studies mainly referring to the advantages and disadvantages of mandatory auditor rotation, are reviewed and discussed in detail. The quantitative research is performed, and find outs that UK public held positive attitudes to mandatory audit firm rotation though mandatory rotation may lead to more audit failures.